A Comparitive Study on Antioxidant Activity of Flavonoids: Structure-Activity Relationships - M, Ajay,; H.M, Cheng,; A.M, Mustafa; M.R, Mustafa (Malaysian Journal of Science, 2005)
In recent times flavonoids received greater attention as a group of "bioactive" compounds because of their potent antioxidant activities. In the present study, the antioxidant activities of several flavonoids have been examined using DPPH and ABTS-free radical scavenging assays. In addition, the ABTS-radical cation scavenging activities of flavonoids were compared with that of vitamin E (Trolox, TEAC). Flavonoids inhibited DPPH-free radicals with varying potency, from highest to lowest: quercetin, fisetin, baicalein, rutin, hesperetin, naringenin, and chrysin. Against the ABTS-free radicals, the order of potency of the flavonoids is (highest to lowest, in brackets TEAC values) quercetin (3.154), rutin (3.032), naringenin (2.686), fisetin (2.578), baicalein (2.237), hesperetin (2.155), chrysin (2.141). Both antioxidant assays demonstrated the free radical scavenging capabilities of flavonoids, and the TEAC values suggest higher potencies for flavonoids compared to vitamin E. The results also suggest that number of hydroxyl substitutions, presence of sugar substitutions and presence of double bond at C-2 and C-3 positions on the basic ring skeleton of the flavonoids are important determinants for antioxidant activity.